Orthographic Activation in L2 Spoken Word Recognition Depends on Proficiency: Evidence from Eye-Tracking - Veivo, Outi; Järvikivi, Juhani; Porretta, Vincent; Hyönä, Jukka (Frontiers in Psychology, 2016)
The use of orthographic and phonological information in spoken word recognition was studied in a visual world task where L1 Finnish learners of L2 French (n = 64) and L1 French native speakers (n = 24) were asked to match spoken word forms with printed words while their eye movements were recorded. In Experiment 1, French target words were contrasted with competitors having a longer (base vs. bague) or a shorter word initial phonological overlap (base vs. bain) and an identical orthographic overlap. In Experiment 2, target words were contrasted with competitors of either longer (mince vs. mite) or shorter word initial orthographic overlap (mince vs. mythe) and of an identical phonological overlap. A general phonological effect was observed in the L2 listener group but not in the L1 control group. No general orthographic effects were observed in the L2 or L1 groups, but a significant effect of proficiency was observed for orthographic overlap over time: higher proficiency L2 listeners used also orthographic information in the matching task in a time-window from 400 to 700ms, whereas no such effect was observed for lower proficiency listeners. These results suggest that the activation of orthographic information in L2 spoken word recognition depends on proficiency in L2.